Development and reutilisation of a fertiliser-based culture medium for the commercial production of Chlorella sorokiniana - Maria Salinas-García; Pablo Calatrava-Arrizabalaga; Martina Ciardi; Silvia Villaró-Cos; Tomás Lafarga (Scientific Reports)
Abstract Microalgae-based processes represent an innovative productive approach in the context of the circular bioeconomy. However, challenges such as the optimisation of production processes need to be addressed for industrial-scale feasibility. In this work, a novel culture medium was developed and specifically designed for Chlorella sorokiniana, a strain with potential for human food consumption. A range of nitrogen sources were tested (nitrate, nitrite, ammonium and urea), with sodium nitrate yielding the fastest growth rate. The optimisation was done in bubble columns with controlled pH (8.0), temperature (25 °C), irradiance (950 µmol m−2 s−1) and aeration (0.2 v/v/min). The nitrogen-to-phosphorus (N:P) molar ratio was then optimised (optimum = 21) and further reductions in macro- and micro-nutrient levels showed no productivity decline, even with micronutrient levels reduced by up to 80%. The final optimised medium resulted in 1.25 g L−1 NaNO3, 0.12 g L−1 K2HPO4, 0.2 g L−1 MgSO4, 0.1 g L−1 CaCl2 and 0.005 g L−1 micronutrients commercial mixture, which produced approximately 4 g L−1 biomass at a rate of 0.3 g L−1 day−1. Then, the exhausted culture medium was recirculated back into the system during semi-continuous cultivation to reduce both water and nutrient requirements. Biomass concentration decreased as the proportion of supernatant recirculation increased, from 3.0 g L−1 without recirculation to 2.2 g L−1 with 70% of supernatant recirculation. Measurements of turbidity, viscosity, total organic carbon and total aerobic mesophylls of the exhausted media highlighted the need for pre-treatment strategies to mitigate the effects of reusing the exhausted culture medium on growth. Future research will refine these strategies to balance cost-effectiveness, productivity, and sustainability in industrial microalgae production.